I Important Indicators in Increasing Buying Interest Electric Vehicles - Eka Pratama, I Gusti Bagus Agung Cahya Diatmika; Martini, Ida Ayu Oka (Dinasti Publisher, 2026)
Electric vehicles are now a promising transportation alternative amidst environmental issues and the threat of fossil fuel scarcity. The government is trying to increase the adoption of electric vehicles through various incentives, but the reality in Bali Province shows that adoption is not in line with expectations. Despite the target of reducing carbon emissions by 41 thousand tons by 2026, with the planned use of 140 thousand motorcycles and 5,719 electric cars, only around 7,752 electric vehicles were registered by August 2024. This study aims to analyze the effect of product quality, price, and after-sales service on the intention to purchase electric vehicles in Bali with brand image as a mediating variable. Using a quantitative approach and purposive sampling, data were collected from 260 respondents who did not yet own an electric vehicle. The analysis was conducted using Microsoft Excel and SmartPLS. The results showed that (1) product quality, price, and after-sales service have a positive and significant effect on brand image; (2) product quality, after-sales service, and brand image have a positive and significant effect on purchase intention, while price has a positive but insignificant effect; and (3) brand image mediates the influence of product quality, price, and after-sales service on interest in purchasing electric vehicles. This conclusion emphasizes the importance of strategic steps by manufacturers and the government to accelerate the adoption of electric vehicles in Bali Province.